2018
DOI: 10.1177/0735633118755494
|View full text |Cite
|
Sign up to set email alerts
|

Missing Piece in Understanding Student Learning: Out-of-School Computer Use

Abstract: Advancements in learning analytics allow teachers to track student learning progress and promote learning by providing necessary intervention and support. Multiple data sources are involved in learning analytics, and the major ones are systems that students use in school. To fully comprehend the progress of student learning, out-of-school learning behaviors should be considered an important part of the academic lives of students. In this study, out-of-school learning behaviors of students, particularly home co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Taking this background into account, we propose the following hypotheses. Fairlie, Beltran, & Das, 2010) and use it daily to facilitate their school work (Gu & Xu, 2019), suggesting that home computers improve educational outcomes and computer skills, leading to more efficient use of computers (Fairlie & London, 2012). Many researchers pointed to a positive impact of computer use in schools on students' educational outcomes (Bayrak & Bayram, 2010;Murillo-Zamorano, López Sánchez, & Godoy-Caballero, 2019;Xiao & Sun, 2021).…”
Section: Computer Attitudesmentioning
confidence: 99%
“…Taking this background into account, we propose the following hypotheses. Fairlie, Beltran, & Das, 2010) and use it daily to facilitate their school work (Gu & Xu, 2019), suggesting that home computers improve educational outcomes and computer skills, leading to more efficient use of computers (Fairlie & London, 2012). Many researchers pointed to a positive impact of computer use in schools on students' educational outcomes (Bayrak & Bayram, 2010;Murillo-Zamorano, López Sánchez, & Godoy-Caballero, 2019;Xiao & Sun, 2021).…”
Section: Computer Attitudesmentioning
confidence: 99%
“…The environment where students learn can affect their attitudes (Hsu and Huang, 2006). Studies have found that students achieve higher grades when they have a computer at home (Fairlie, 2012;Fairlie et al, 2010) and use it daily to facilitate their school work (Gu and Xu, 2019), suggesting that home computers improve educational outcomes and computer skills, leading to more efficient use of computers (Fairlie and London, 2012). Many researchers pointed to a positive impact of computer use in schools on students' educational outcomes (Bayrak and Bayram, 2010;Murillo-Zamorano et al, 2019;Xiao and Sun, 2021).…”
Section: Learning Environments and Motivationsmentioning
confidence: 99%
“…Unlike the use of Information and Communication Technologies (ICTs) in schools, the home use of digital technologies by children and its effects have remained an under-researched area (Wang & Minghao, 2012). This is striking since nowadays (informal) learning occurs not only at schools but also out-of-school at home (see Noroozi et al, 2012Noroozi et al, , 2016Gu & Xu, 2018). This gives a false picture of the extent of ownership and use of computers by children at home -which will soon reach saturation point in England, with one computer per child at home (McPake, Ploman & Stephen, 2013) compared to a lower rate of availability of computers and their limited use in schools.…”
Section: Introductionmentioning
confidence: 99%